Augustus Alvord correspondence - Alvord, Augustus, 1834-1904.
Letter.
Soldier.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Alvord, Augustus, -- 1834-1904 -- Correspondence; Soldiers